Ethnicity and social categorization in on- and offline interaction among Copenhagen adolescents. (June 2015) - Rørbeck Nørreby, Thomas; Spindler Møller, Janus
Abstract: In this paper, we investigate how adolescents living in late modern Copenhagen use and organize identity categories related to ethnicity in everyday interaction. From a perspective of linguistic ethnography we analyze exchanges where ethnicity is explicitly addressed in activities such as creating and maintaining friendship ties, teasing, flirting, etc. We show how ethnicity is brought about in media trends on Facebook, how it becomes associated with hip hop culture, how it is used in constructions of beauty and desirability, and how a societal discourse of ethnocentricity have consequences for patterns of identification, but also make up a resource in everyday interaction. We present data from one year of fieldwork among a group of pupils all attending the same school class with a special focus on two individuals and analyze three thematically interrelated key cases against the backdrop of the patterns we observe in the year-long data material. We show how our participants treat ethnicity as something to play around with, negotiate, transcend and create new versions of. At the same time though, we also find in our data instances in which our participants bring into play traditional "old-school" ethnicities and thereby mobilize fixed categories ideologically associated with authenticity as an actual aspect of ethnicization (Brubaker, 2004. Ethnicity without groups. Harvard University Press, Cambridge). In line with Otsuji and Pennycook (2010. Int. J. Multiling.7(3), 240–254) we therefore argue that fixed and fluid ethnicity categories are not brought into play as dichotomies but rather as symbiotically (re)constituting each other. Highlights: Adolescents in late modern Copenhagen frequently use and negotiate identity categories associated with ethnicity. The participants sometimes treat ethnicity as dynamic and negotiable; and sometimes as linked to essentialist notions of authenticity. Ethnicity interplays with other identity resources in constructions of being cool, being young, being desirable etc.